Sosialisasi dan Edukasi Anti-Bullying pada Remaja: Membangun Solidaritas Menuju Generasi Emas - Adela Salsabila; Try Adhi Bangsawan; Dody Darly; Warto, Warto; Ananda Dyta Marlina Setiawan; Tubagus Ilham Nugaraha (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Bullying and juvenile delinquency are social phenomena that not only negatively impact individual psychological and emotional development but also have broad implications for social harmony, school stability, and the quality of the future generation of young people. This situation demands systematic and structured efforts to prevent and address it, so that adolescents can develop in a safe, healthy, and supportive environment. The community service program implemented in Mekarsari Village, Sajira District, Lebak Regency, Banten, was implemented in response to this need, with the primary goal of increasing awareness, knowledge, and skills in preventing bullying and juvenile delinquency among junior high school students and their accompanying teachers. The program was designed using interactive outreach methods, group discussions, role-playing, and ongoing mentoring that emphasized the active involvement of all participants. The results of the activity showed a significant increase in participants' understanding of the definitions, types, impacts, and strategies for handling bullying and juvenile delinquency. Furthermore, the program succeeded in bringing about real changes in student behavior, marked by a decrease in conflict, increased positive communication, and the growth of a culture of mutual respect in the school environment. One manifestation of creativity in this program is the symbolic activity of handprinting with colored paint on a large banner as a declaration of collective commitment to fight bullying. Positive impacts are also seen in teachers who are better prepared to identify potential problematic behavior and provide appropriate guidance to their students. The environment of SMP Negeri 4 Sajira is now beginning to show a safer, more conducive, and supportive atmosphere for adolescent development. In conclusion, this community service activity has proven effective in raising awareness, changing behavior, and building a shared commitment to fight bullying and juvenile delinquency. Therefore, similar programs are highly recommended for replication in other schools to create a stronger, more integrated, and positively competitive young generation.